2008
DOI: 10.4103/0971-6203.39417
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric evaluation of rectum and bladder using image-based CT planning and orthogonal radiographs with ICRU 38 recommendations in intracavitary brachytherapy

Abstract: The purpose is to compare CT-based dosimetry with International Commission on Radiation Units and Measurements (ICRU 38) bladder and rectum reference points in patients of carcinoma of uterine cervix treated with intracavitary brachytherapy (ICA). Twenty-two consecutive patients were evaluated. Orthogonal radiographs and CT images were acquired and transferred to PLATO planning system. Bladder and rectal reference points were identified according to ICRU 38 recommendations. Dosimetry was carried out based on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 41 publications
3
27
1
Order By: Relevance
“…[12] (62 HDR applications), Jamema et al . [13], (22 HDR applications) (both authors prescribed 7 Gy dose at Point A) as well as with Tan et al . [14] (55 applications with 5.3 Gy to Point A).…”
Section: Discussionmentioning
confidence: 94%
“…[12] (62 HDR applications), Jamema et al . [13], (22 HDR applications) (both authors prescribed 7 Gy dose at Point A) as well as with Tan et al . [14] (55 applications with 5.3 Gy to Point A).…”
Section: Discussionmentioning
confidence: 94%
“…A major drawback of orthogonal x-rayYbased 2D planning is the inability to calculate and estimate dose to upper rectum and rectosigmoid, and these regions are known for late morbidity. 12,19,24 To date, these regions can only be evaluated by 3D DVH analysis using either CT or MRI. In our study, the rectal DVH parameters are lower than those reported (Table 3).…”
Section: Rectal and Sigmoid Dosesmentioning
confidence: 99%
“…[7] However, these facilities are limited to only a few urban centers. Rural centers in particular lack these facilities.…”
Section: Discussionmentioning
confidence: 99%